Chemical nickel plating solution and chemical nickel plating process

By using specific proportional components in electroless nickel plating solution, the problems of slow plating speed and poor stability are solved, and the uniformity, density and performance of the plating are improved, which is suitable for large-scale production.

CN118957553BActive Publication Date: 2025-02-14HUIZHOU JINSHENG NEW ELECTRONIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410976496.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-20
Publication Date
2025-02-14
Estimated Expiration
2044-07-20

AI Technical Summary

Technical Problem

The electroless nickel plating process has a slow plating speed and poor stability of the plating solution, resulting in uneven plating quality, limiting its application in large-scale production.

Method used

Using specific ratios of electroless nickel plating liquid components, including nickel salts, reducing agents, pyridines, accelerators, complexing agents, buffers, stabilizers, composite leveling agents, surfactants, adhesion stabilizers and nanocomposite metal particles , through the synergistic effect of these components, the nickel plating speed and stability are improved.

Benefits of technology

The nickel plating speed has been improved, the uniformity and density of the plating layer have been significantly improved, and the hardness, wear resistance and corrosion resistance of the plating layer have also been improved, meeting the needs of large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004954700130000101
    Figure BDA0004954700130000101
  • Figure BDA0004954700130000111
    Figure BDA0004954700130000111
Patent Text Reader

Abstract

The present application relates to the technical field of chemical nickel plating, and more specifically, to a chemical nickel plating solution and a chemical nickel plating treatment process. According to mass concentration, 6-10 g / L of nickel salt, 18-22 g / L of reducing agent, 2-3 g / L of pyridine, 0.02-0.04 g / L of accelerator, 25-30 g / L of complexing agent, 25-35 g / L of buffer, 0.1-0.4 g / L of stabilizer, 2-5 g / L of composite leveler, 0.06-0.1 g / L of surfactant, 0.1-0.3 g / L of adhesion stabilizer, and 1-2 g / L of nanocomposite metal particles are prepared from raw materials including the following parts by weight. The composite leveler is prepared by mixing hydroxylated propane sulfonic acid pyridinium salt and propargyl alcohol ether in a weight ratio of 1:(0.5-0.8). By adopting the above formula, a chemical nickel plating solution is prepared, which has fast nickel plating speed and good stability, and can form a uniform, dense, wear-resistant and corrosion-resistant nickel layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of chemical nickel plating, and more specifically, to a chemical nickel plating solution and a chemical nickel plating treatment process. Background Art

[0002] Chemical nickel plating is a surface treatment technology that deposits a nickel layer on a metal surface by chemical methods. Chemical nickel plating can form a uniform coating on workpieces with complex shapes and structures, especially in areas such as grooves, holes and gaps that are difficult to reach by traditional electroplating. The obtained chemical nickel plating layer has high hardness, good wear resistance and good corrosion resistance. Therefore, the chemical nickel plating process is widely used in electronic components, automotive industry, aerospace and other fields.

[0003] At present, the chemical nickel plating process has a slower plating speed than electrolytic nickel plating. At the same time, the chemical nickel plating solution used in chemical nickel plating has poor stability, which will lead to uneven coating quality and even defects during the nickel plating process, which limits its application in large-scale production. Summary of the invention

[0004] In order to solve the problems of short chemical nickel plating process time and poor stability of chemical nickel plating solution, the present application provides a chemical nickel plating solution and a chemical nickel plating process.

[0005] In a first aspect, the present application provides a chemical nickel plating solution, which adopts the following technical solution:

[0006] A chemical nickel plating solution is prepared from the following raw materials in parts by weight:

[0007] Nickel salt 6-10g / L

[0008] Reducing agent 18-22g / L

[0009] Pyridine 2-3g / L

[0010] Accelerator 0.02-0.04g / L

[0011] Complexing agent 25-30g / L

[0012] Buffer 25-35g / L

[0013] Stabilizer 0.1-0.4g / L

[0014] Composite leveling agent 2-5g / L

[0015] Surfactant 0.06-0.1g / L

[0016] Adhesion stabilizer 0.1-0.3g / L

[0017] Nanocomposite metal particles 1-2g / L

[0018] The composite leveling agent is prepared by mixing hydroxylated propane sulfonic acid pyridinium salt and propargyl alcohol ether in a weight ratio of 1:(0.5-0.8).

[0019] By adopting the technical solution, a chemical nickel plating solution is prepared, which has a fast nickel plating speed, good stability, and can form a uniform and dense nickel layer.

[0020] Among them, nickel salt provides nickel ions to ensure the normal progress of nickel plating. The reducing agent can reduce nickel ions to metallic nickel, thereby forming a nickel plating layer on the surface of the substrate. Pyridine can form a complex with nickel ions to reduce the activity of nickel ions, thereby adjusting the deposition rate of the nickel plating layer and making the nickel plating layer more uniform and smooth. The accelerator can accelerate the nickel plating process and increase the deposition rate of the plating layer. The complexing agent can form a stable complex with nickel ions to prevent the nickel ions from hydrolyzing and precipitating in the plating solution and ensure the quality of nickel plating. The buffer can adjust the pH value of the plating solution, maintain the acid-base balance of the plating solution, and prevent the plating solution from affecting the quality of the nickel plating layer due to changes in pH value during the nickel plating process. The stabilizer can prevent the plating solution from decomposing and precipitating during storage and use, reduce the generation of impurities in the plating layer, and improve the uniformity and density of the nickel plating layer. The surfactant can reduce the interfacial tension between the plating solution and the substrate, making it easier for the plating solution to spread and wet on the surface of the substrate. Adhesion stabilizers can enhance the bonding force between the coating and the substrate, prevent the coating from falling off or peeling during subsequent processing and use, and improve the corrosion resistance and wear resistance of the nickel coating. Nanocomposite metal particles can serve as a reinforcing phase in the nickel coating to improve the hardness, wear resistance and corrosion resistance of the nickel coating. At the same time, nanocomposite metal particles can serve as an effective catalyst in the chemical nickel plating process due to their high specific surface area and active sites, promoting the reduction and deposition of nickel ions, thereby improving the deposition rate and uniformity of the coating.

[0021] The composite leveling agent is prepared by mixing hydroxylated propane sulfonic acid pyridinium salt and propargyl alcohol ether in a certain proportion, and can improve the surface flatness and glossiness of the coating and reduce pinholes and pits in the coating.

[0022] Preferably, the nanocomposite metal particles are prepared by the following method:

[0023] A: Under nitrogen conditions, copper, zinc and tin are melted and then cooled to obtain a composite metal, wherein the mass fraction of copper is 50%-60%, the mass fraction of zinc is 30%-45%, and the rest is tin;

[0024] B: crushing the composite metal to nanometer scale with an average particle size of 50-100nm to obtain nano composite metal;

[0025] C: Soak the nanocomposite metal in a weak acid solution for 3-5 hours, take it out, and dry it to obtain nanocomposite metal particles.

[0026] By adopting the above technical solution, the prepared nanocomposite metal particles can improve the wear resistance, hardness and corrosion resistance of the nickel plating layer. By preparing an alloy from copper, zinc and tin in step A, the wear resistance and corrosion resistance of the composite metal particles can be further improved. Among them, tin plays a lubricating role in the molten state, promotes the compatibility of copper and zinc, and is conducive to the synthesis of the alloy.

[0027] The alloy is crushed to nanometer scale in step B, thereby increasing its high specific surface area and active sites, thereby promoting the reduction and deposition of nickel ions and improving the deposition rate and uniformity of the coating.

[0028] In step C, oxides or other impurities on the surface of the nanocomposite metal are removed to improve the activity and stability of the nanoparticles.

[0029] Preferably, the nickel salt is nickel sulfate and / or nickel acetate.

[0030] The adoption of the above technical solution is beneficial to improving the speed of nickel plating.

[0031] Preferably, the accelerator is obtained by mixing p-hydroxybenzenesulfonate and guanidine hydrochloride in a weight ratio of (6-9):2.

[0032] By adopting the above technical solution, p-hydroxybenzenesulfonate and guanidine hydrochloride may adsorb and complex with nickel ions in the plating solution. Guanidine hydrochloride can promote the transfer of nickel ions through ion exchange. The two work together to increase the deposition rate of the nickel plating layer, form a denser and more uniform plating layer, shorten the nickel plating cycle, and improve production efficiency. At the same time, adjusting the composition of the accelerator can optimize the properties of the plating layer, such as thickness, uniformity and adhesion.

[0033] Preferably, the reducing agent is obtained by mixing sodium hypophosphite, glyoxal and hydrazine in a weight ratio of (3-5):(1-2):2.

[0034] By adopting the above technical solution, sodium hypophosphite, glyoxal and hydrazine produce a synergistic effect in the plating solution, jointly promote the reduction reaction of nickel ions, can provide stronger reducing ability, promote the reduction reaction of nickel ions, and thus improve the efficiency of nickel plating. Hydrazine and glyoxal can obtain a nickel plating layer with higher purity. In addition, sodium hypophosphite will simultaneously precipitate phosphorus during the reduction process to form a nickel-phosphorus alloy coating with nickel. This alloy coating usually has better corrosion resistance and mechanical properties.

[0035] Preferably, the stabilizer is obtained by mixing cerium sulfate, potassium hexacyanoferrate and thiourea in a weight ratio of (2-3): (1-2): 3.

[0036] By adopting the above technical scheme, cerium sulfate and potassium hexacyanoferrate can undergo redox reaction with the reducing agent in the plating solution to adjust the redox potential in the plating solution; thiourea can reduce the oxidizing property in the plating solution, thereby reducing the spontaneous decomposition of the plating solution; the mixture of cerium sulfate, potassium hexacyanoferrate and thiourea can significantly inhibit the spontaneous decomposition reaction in the plating solution, ensure that the plating solution remains stable for a long time, and prevent the plating solution from decomposing in a short period of time and causing performance degradation.

[0037] Preferably, the adhesion stabilizer is prepared by mixing potassium antimony tartrate and alginic acid in a weight ratio of (4-6):3.

[0038] By adopting the above technical solution, the mixture of potassium antimony tartrate and alginic acid is used as an adhesion stabilizer, which can significantly improve the adhesion between the coating and the substrate, prevent the nickel coating from peeling or cracking during use, and improve the durability and reliability of the plated parts. Potassium antimony tartrate and alginic acid can also form a stable complex with nickel ions in the plating solution. This complex can reduce the concentration of free nickel ions in the plating solution, reduce impurities and defects in the coating, and improve the uniformity and density of the coating.

[0039] Preferably, the buffer is at least one of acetic acid, phosphoric acid, lactic acid or oxalic acid.

[0040] By adopting the above technical solution, the pH value of the chemical nickel plating solution can be effectively adjusted and controlled to maintain it within an appropriate range, and the deposition rate of nickel ions can be adjusted to make it more uniform, thereby obtaining a smoother and more uniform coating and avoiding dense and loose phenomena.

[0041] Preferably, the surfactant is a polyether polyol.

[0042] Polyether polyols help improve the wettability and spreadability of the plating solution on the metal surface, reduce the retention and adsorption of bubbles on the surface of the plated part, and enable the plating solution to cover the metal surface more evenly. At the same time, polyether polyols can enhance the dispersibility of other components in the plating solution, ensure the uniform distribution of various components in the plating solution, avoid precipitation and agglomeration, thereby improving the stability of the plating solution and the quality of the coating.

[0043] In a second aspect, the present application provides a chemical nickel plating process, which adopts the following technical solution:

[0044] A chemical nickel plating process comprises the following steps:

[0045] S1: Pretreatment, including cleaning and activating the surface of metal parts, removing oil and oxides on the surface;

[0046] S2: preparing a chemical nickel plating solution, mixing nickel salt, reducing agent, pyridine, accelerator, complexing agent, buffer, stabilizer, composite leveling agent, surfactant, adhesion stabilizer, nanocomposite metal particles and deionized water to obtain a chemical nickel plating solution; S3: immersing the pre-treated metal part in the chemical nickel plating solution to perform a nickel-gold reaction until a uniform nickel-gold alloy layer is formed on the metal surface;

[0047] S4: Take out the metal parts and perform post-processing, including cleaning, drying and other steps to remove the chemical nickel plating solution remaining on the surface.

[0048] By adopting the above technical solution, nickel plating can be completed quickly, and the obtained nickel plating layer is uniform and compact, and has good hardness, corrosion resistance and adhesion.

[0049] In summary, this application has the following beneficial effects:

[0050] 1. Fast nickel plating speed: The nickel plating speed of chemical nickel plating solution can be greatly improved through the cooperation of various components.

[0051] 2. Good quality of nickel plating: The obtained nickel plating layer is dense, flat and uniform, avoids smoothness, has good coating adhesion and wear resistance, and meets the requirements of functional chemical nickel plating.

[0052] 3. Smooth surface of nickel-plated layer: The use of composite leveling agent significantly improves the surface quality of nickel-plated layer. The mixed use of hydroxylated propane sulfonic acid pyridinium salt and propargyl alcohol ether reduces the surface defects of nickel-plated layer, such as pinholes and pitting, and improves the gloss and smoothness of the coating.

[0053] 4. Long service life: The addition of nano-composite metal particles can enhance the hardness, wear resistance and corrosion resistance of the coating and improve the service life of the coating. DETAILED DESCRIPTION

[0054] Example

[0055] Example 1

[0056] A chemical nickel plating process comprises the following steps:

[0057] S1: Pretreatment, including cleaning and activating the metal surface, removing surface oil and oxides;

[0058] S2: Prepare a chemical nickel plating solution, and stir 60 g of nickel salt (nickel sulfate), 180 g of reducing agent, 20 g of pyridine, 0.2 g of accelerator, 250 g of complexing agent (sodium diethylenetriamine pentacarboxylate), 250 g of buffer (acetic acid), 1 g of stabilizer, 20 g of composite leveler, 0.6 g of surfactant (polyether polyol), 1 g of adhesion stabilizer, 10 g of nanocomposite metal particles and 10 L of deionized water to obtain a chemical nickel plating solution;

[0059] S3: immersing the pre-treated metal part in a chemical nickel plating solution to perform a nickel-gold reaction until a uniform nickel-gold alloy layer is formed on the metal surface;

[0060] S4: Take out the metal parts and perform post-processing, including cleaning, drying and other steps to remove the chemical nickel plating solution remaining on the surface.

[0061] The composite leveling agent is prepared by mixing hydroxylated propane sulfonic acid pyridinium salt and propargyl alcohol ether in a weight ratio of 1:0.5.

[0062] The accelerator is obtained by mixing p-hydroxybenzenesulfonate and guanidine hydrochloride in a weight ratio of 6:2.

[0063] The reducing agent is obtained by mixing sodium hypophosphite, glyoxal and hydrazine in a weight ratio of 3:1:2.

[0064] The stabilizer is obtained by mixing cerium sulfate, potassium hexacyanoferrate and thiourea in a weight ratio of 2:1:3.

[0065] The adhesion stabilizer is prepared by mixing potassium antimony tartrate and alginic acid in a weight ratio of 4:3.

[0066] The polyether polyol was purchased from Shanghai Kaiyin Chemical Co., Ltd., model VORANOL 2120.

[0067] The nano composite metal particles are obtained by mixing nano copper, nano zinc and nano tin according to weight percentages of 50%, 45% and 5%.

[0068] The average particle size of nano-copper, nano-zinc and nano-tin is 50nm.

[0069] Example 2

[0070] A chemical nickel plating process comprises the following steps:

[0071] S1: Pretreatment, including cleaning and activating the metal surface, removing surface oil and oxides;

[0072] S2: preparing a chemical nickel plating solution, mixing 80 g of nickel salt (nickel sulfate), 200 g of reducing agent, 25 g of pyridine, 0.3 g of accelerator, 280 g of complexing agent (disodium EDTA), 300 g of buffer (acetic acid), 2 g of stabilizer, 40 g of composite leveler, 0.8 g of surfactant (polyether polyol), 2 g of adhesion stabilizer, 15 g of nanocomposite metal particles and 10 L of deionized water to obtain a chemical nickel plating solution;

[0073] S3: immersing the pre-treated metal part in a chemical nickel plating solution to perform a nickel-gold reaction until a uniform nickel-gold alloy layer is formed on the metal surface;

[0074] S4: Take out the metal parts and perform post-processing, including cleaning, drying and other steps to remove the chemical nickel plating solution remaining on the surface.

[0075] The composite leveling agent is prepared by mixing hydroxylated propane sulfonic acid pyridinium salt and propargyl alcohol ether in a weight ratio of 1:0.6.

[0076] The accelerator is obtained by mixing p-hydroxybenzene sulfonate (sodium p-hydroxybenzene sulfonate) and guanidine hydrochloride in a weight ratio of 7:2.

[0077] The reducing agent is obtained by mixing sodium hypophosphite, glyoxal and hydrazine in a weight ratio of 4:1.5:2.

[0078] The stabilizer is obtained by mixing cerium sulfate, potassium hexacyanoferrate and thiourea in a weight ratio of 2.5:1.5:3.

[0079] The adhesion stabilizer is prepared by mixing potassium antimony tartrate and alginic acid in a weight ratio of 5:3.

[0080] Polyether polyol was purchased from Nantong Renda Chemical Co., Ltd., model F-68.

[0081] The nano composite metal particles are obtained by mixing nano copper, nano zinc and nano tin according to weight percentages of 55%, 40% and 5%.

[0082] The average particle size of nano copper, nano zinc and nano tin is 100nm

[0083] Example 3

[0084] A chemical nickel plating process comprises the following steps:

[0085] S1: Pretreatment, including cleaning and activating the surface of metal parts, removing oil and oxides on the surface;

[0086] S2: preparing a chemical nickel plating solution, mixing 100 g of nickel salt (nickel sulfate), 220 g of reducing agent, 30 g of pyridine, 0.4 g of accelerator, 300 g of complexing agent (sodium nitrilotriacetate), 350 g of buffer (acetic acid), 4 g of stabilizer, 50 g of composite leveler, 1 g of surfactant (polyether polyol), 3 g of adhesion stabilizer, 20 g of nanocomposite metal particles and 10 L of deionized water to obtain a chemical nickel plating solution;

[0087] S3: immersing the pre-treated metal part in a chemical nickel plating solution to perform a nickel-gold reaction until a uniform nickel-gold alloy layer is formed on the metal surface;

[0088] S4: Take out the metal parts and perform post-processing, including cleaning, drying and other steps to remove the chemical nickel plating solution remaining on the surface.

[0089] The composite leveling agent is prepared by mixing hydroxylated propane sulfonic acid pyridinium salt and propargyl alcohol ether in a weight ratio of 1:0.8.

[0090] The accelerator is obtained by mixing p-hydroxybenzenesulfonate and guanidine hydrochloride in a weight ratio of 9:2.

[0091] The reducing agent is obtained by mixing sodium hypophosphite, glyoxal and hydrazine in a weight ratio of 5:1:2.

[0092] The stabilizer is obtained by mixing cerium sulfate, potassium hexacyanoferrate and thiourea in a weight ratio of 3:2:3.

[0093] The adhesion stabilizer is prepared by mixing potassium antimony tartrate and alginic acid in a weight ratio of 6:3.

[0094] The polyether polyol was purchased from Nantong Renda Chemical Co., Ltd., model F-68.

[0095] The nano composite metal particles are obtained by mixing nano copper, nano zinc and nano tin according to weight percentages of 60%, 30% and 10%.

[0096] Example 4

[0097] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the nanocomposite metal particles are prepared by the following method:

[0098] A: Under nitrogen conditions, 10g of copper, 9g of zinc and 1g of tin are melted and cooled to obtain a composite metal, in which the mass fraction of copper is 50%, the mass fraction of zinc is 45%, and the rest is tin;

[0099] B: crushing the composite metal to nanometer scale with an average particle size of 50nm to obtain nano composite metal;

[0100] C: Soak the nanocomposite metal in a weak acid solution (acetic acid solution with a mass fraction of 15%) for 3 hours, take it out, and dry it to obtain nanocomposite metal particles.

[0101] Example 5

[0102] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the nanocomposite metal particles are prepared by the following method:

[0103] A: Under nitrogen conditions, 12g of copper, 6g of zinc and 2g of tin are melted and cooled to obtain a composite metal, wherein the mass fraction of copper is 60%, the mass fraction of zinc is 30%, and the rest is tin;

[0104] B: crushing the composite metal to nanometer scale with an average particle size of 100nm to obtain nano composite metal;

[0105] C: Soak the nanocomposite metal in a weak acid solution (acetic acid solution with a mass fraction of 15%) for 5 hours, take it out, and dry it to obtain nanocomposite metal particles.

[0106] Example 6

[0107] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the accelerator is p-hydroxybenzene sulfonate.

[0108] Example 7

[0109] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the accelerator is guanidine hydrochloride.

[0110] Example 8

[0111] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the reducing agent is sodium hypophosphite.

[0112] Example 9

[0113] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the reducing agent is glyoxal.

[0114] Example 10

[0115] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the reducing agent is hydrazine.

[0116] Embodiment 11

[0117] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the reducing agent is obtained by mixing sodium hypophosphite and glyoxal in a weight ratio of 3:3.

[0118] Example 12

[0119] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the reducing agent is obtained by mixing sodium hypophosphite and hydrazine in a weight ratio of 3:3.

[0120] Embodiment 13

[0121] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the reducing agent is obtained by mixing glyoxal and hydrazine in a weight ratio of 3:5.

[0122] Embodiment 14

[0123] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the stabilizer is cerium sulfate.

[0124] Embodiment 15

[0125] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the stabilizer is potassium hexacyanoferrate.

[0126] Example 16

[0127] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the stabilizer is thiourea.

[0128] Embodiment 17

[0129] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the stabilizer is obtained by mixing cerium sulfate and potassium hexacyanoferrate in a weight ratio of 2:5.

[0130] Embodiment 18

[0131] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the stabilizer is obtained by mixing cerium sulfate and thiourea in a weight ratio of 2:5.

[0132] Embodiment 19

[0133] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the stabilizer is obtained by mixing potassium hexacyanoferrate and thiourea in a weight ratio of 1:5.

[0134] Embodiment 20

[0135] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the adhesion stabilizer is potassium antimony tartrate.

[0136] Embodiment 21

[0137] A chemical nickel plating process, the difference between this embodiment and embodiment 1 is that the adhesion stabilizer is alginate.

[0138] Comparative Example

[0139] Comparative Example 1

[0140] A chemical nickel plating process, the difference between this comparative example and Example 1 is that no pyridine is added.

[0141] Comparative Example 2

[0142] A chemical nickel plating process, the difference between this comparative example and Example 1 is that no accelerator is added.

[0143] Comparative Example 3

[0144] A chemical nickel plating process, the difference between this comparative example and Example 1 is that no composite leveling agent is added.

[0145] Comparative Example 4

[0146] A chemical nickel plating process, the difference between this comparative example and Example 1 is that the composite leveler is hydroxylated propane sulfonic acid pyridinium salt.

[0147] Comparative Example 5

[0148] A chemical nickel plating process, the difference between this comparative example and Example 1 is that the composite leveling agent is propargyl alcohol ether.

[0149] Comparative Example 6

[0150] A chemical nickel plating process, the difference between this comparative example and Example 1 is that the composite leveler is obtained by mixing hydroxylated propane sulfonic acid pyridinium salt and propargyl alcohol ether in a weight ratio of 1:1.

[0151] Comparative Example 7

[0152] A chemical nickel plating process, the difference between this comparative example and Example 1 is that no adhesion stabilizer is added.

[0153] Comparative Example 8

[0154] A chemical nickel plating process, the difference between this comparative example and Example 1 is that no nano composite metal particles are added.

[0155] Performance testing

[0156] The samples prepared in Examples 1-21 and Comparative Examples 1-8 were subjected to salt spray test, adhesion test, hardness test and appearance test;

[0157] The chemical nickel plating solutions prepared in Examples 1-21 and Comparative Examples 1-8 were subjected to plating speed tests and stability tests.

[0158] Detection method / test method Plating speed: After the plating solution in step S3 is used, the plating is continued for 1 hour, and then the coating thickness at 5-8 points is measured by an X-ray fluorescence instrument (XRF), and the average value is taken in μm / h.

[0159] Salt spray test: refer to GB / T2423.17-93 medium salt spray test standard (NSS) and the conditions are as follows: the salt solution uses 5% sodium chloride, the pH is between 6.5-7.2, continuous atomization is used, the temperature is maintained at 35°C, and the salt spray deposition rate is maintained at 1.5mL / (h.80cm 2 ) and observe whether there is peeling, cracking, wrinkling, and bubbles.

[0160] Adhesion performance test: Use a hard steel scratcher with a 30-degree sharp angle to scratch two parallel lines 2 mm apart on the coating surface, and observe whether the coating between the scratch lines is lifted or peeled off; if not, bake at 150 degrees Celsius for 200 minutes and observe whether the coating between the scratch lines is lifted or peeled off.

[0161] Hardness test: Vickers hardness (HV, kg / mm 2 ) indicates that the greater the hardness, the higher the wear resistance. The hardness of the coating is measured with a Vickers hardness tester. The better the hardness, the more wear-resistant it is.

[0162] Stability test: Preparation of 0.1g / L palladium chloride solution: weigh 5g of ammonium chloride, dissolve it in 20mL of deionized water, add 0.1000g of palladium chloride, and adjust the volume to 1L after it is fully dissolved.

[0163] Take 50mL of the nickel plating solution to be tested and place it in a 100mL test tube. Immerse the test tube in a water bath at 85℃. The liquid level in the test tube is 2cm below the water bath level. Half an hour later, under stirring, use a pipette to measure 1mL of 0.1g / L palladium chloride solution into the test tube. Under natural light conditions, record the time it takes for the nickel plating solution to be tested to turn black after the palladium chloride solution is injected into the test tube. The longer the time, the better the stability of the nickel plating solution to be tested.

[0164] Appearance inspection: observe the appearance of the magnesium alloy substrate after nickel plating to see whether the coating is uniform, whether there are pinholes, plating leakage and other phenomena. The experimental data are shown in Table 1:

[0165] Table 1 Experimental data of Examples 1-21 and Comparative Examples 1-8

[0166]

[0167]

[0168] By comparing Example 1 with Comparative Examples 1-3 and 7-8, the plating speed in Example 1 is fast, and no wrinkling, peeling, cracking, bubbles, etc. are found after salt spray resistance speed measurement; no warping or peeling occurs in Example 1 after adhesion performance test; the hardness in Example 1 is also higher than that in Comparative Examples 1-3 and 7-8; the nickel plating layer in Example 1 is uniform, indicating that the nickel plating speed of the chemical nickel plating solution is further improved by the formula in the present application, while ensuring that the nickel plating layer is uniform and has good hardness, adhesion performance and corrosion resistance.

[0169] Comparing Example 1 with Comparative Examples 3-6, the nickel plating speed in Comparative Example 3-5 is significantly lower than that in Example 1; Comparative Example 3-6 exhibits peeling, cracking and bubbling in the salt spray resistance test; Comparative Example 3-5 exhibits peeling and warping in the adhesion performance test; the hardness of Comparative Example 3-4 is not as good as that of Example 1; and plating leakage occurs in Comparative Example 3-6, indicating that in the present application, by using hydroxylated propane sulfonic acid pyridinium salt and propargyl alcohol ether in a specific proportion, the nickel plating speed of the chemical nickel plating solution can be further improved, while ensuring that the nickel plating layer is uniform and has good hardness, adhesion and corrosion resistance.

[0170] Comparing Example 1 with Example 4-5, the nickel plating speed of Example 4-5 is significantly improved; in the adhesion performance test, the good adhesion performance is maintained even after the heating test, and no abnormal phenomenon occurs; the hardness is significantly improved in Example 4-5; the stability test time of the chemical nickel plating solution of Example 4-5 is improved, indicating that the nano-composite metal particles prepared by the present application can improve the nickel plating speed and stability of the chemical nickel plating solution, while ensuring that the nickel plating layer is uniform and has good hardness and adhesion performance.

[0171] Comparing Example 1 with Example 6-7, the nickel plating speed of Example 6-7 is lower than that of Example 1, and the stability test time of the chemical nickel plating solution of Example 6-7 is lower than that of Example 1, indicating that the nickel plating speed and stability of the chemical nickel plating solution can be improved by using p-hydroxybenzenesulfonate and guanidine hydrochloride in a specific proportion.

[0172] Comparing Example 1 with Example 8-13, the nickel plating speed in Example 8-10 is lower than that in Example 1; the hardness in Example 8-13 is lower than that in Example 1; and the stability test time of the chemical nickel plating solution in Example 8-13 is lower than that in Example 1, indicating that by mixing sodium hypophosphite, glyoxal and hydrazine, the nickel plating speed and stability of the chemical nickel plating solution can be improved, and the hardness of the coating can be improved.

[0173] Comparing Example 1 with Example 14-19, the nickel plating speed in Example 14-19 is lower than that in Example 1; the hardness in Example 14-19 is lower than that in Example 1; the stability test time of the chemical nickel plating solution in Example 14-19 is lower than that in Example 1, indicating that the mixed use of cerium sulfate, potassium hexacyanoferrate and thiourea can improve the nickel plating speed and stability of the chemical nickel plating solution, while improving the hardness of the coating.

[0174] Comparing Example 1 with Example 20-21, the nickel plating speed in Example 20-21 is lower than that in Example 1; the hardness in Example 20-219 is lower than that in Example 1; the stability test time of the chemical nickel plating solution in Example 20-21 is lower than that in Example 1, indicating that mixing potassium antimony tartrate and alginic acid can improve the nickel plating speed and stability of the chemical nickel plating solution, while improving the hardness of the coating.

[0175] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A chemical nickel plating solution, characterized in that The preparation method is based on the following raw materials in parts by weight: Nickel salt 6-10g / L Reducing agent 18-22g / L Pyridine 2-3g / L Accelerator 0.02-0.04g / L Complexing agent 25-30g / L Buffer 25-35g / L Stabilizer 0.1-0.4g / L Composite leveling agent 2-5g / L Surfactant 0.06-0.1g / L Adhesion stabilizer 0.1-0.3g / L Nanocomposite metal particles 1-2g / L The composite leveling agent is obtained by mixing hydroxylated propane sulfonic acid pyridinium salt and propargyl alcohol ether in a weight ratio of 1: (0.5-0.8); The reducing agent is obtained by mixing sodium hypophosphite, glyoxal and hydrazine in a weight ratio of (3-5): (1-2):

2.

2. A chemical nickel plating solution according to claim 1, characterized in that: The nanocomposite metal particles are prepared by the following method: A: Under nitrogen conditions, copper, zinc and tin are melted and then cooled to obtain a composite metal, in which the mass fraction of copper is 50%-60%, the mass fraction of zinc is 30%-45%, and the rest is tin; B: crushing the composite metal to nanometer scale with an average particle size of 50-100nm to obtain nano composite metal; C: Soak the nanocomposite metal in a weak acid solution for 3-5 hours, take it out, and dry it to obtain nanocomposite metal particles.

3. A chemical nickel plating solution according to claim 2, characterized in that, The nickel salt is nickel sulfate and / or nickel acetate.

4. A chemical nickel plating solution according to claim 1, characterized in that: The accelerator is obtained by mixing p-hydroxybenzenesulfonate and guanidine hydrochloride in a weight ratio of (6-9):

2.

5. A chemical nickel plating solution according to claim 1, characterized in that: The stabilizer is obtained by mixing cerium sulfate, potassium hexacyanoferrate and thiourea in a weight ratio of (2-3): (1-2):

3.

6. A chemical nickel plating solution according to claim 1, characterized in that: The adhesion stabilizer is prepared by mixing potassium antimony tartrate and alginic acid in a weight ratio of (4-6):

3.

7. A chemical nickel plating solution according to claim 1, characterized in that: The buffer is at least one of acetic acid, phosphoric acid, lactic acid or oxalic acid.

8. A chemical nickel plating solution according to claim 1, characterized in that: The surfactant is polyether polyol.

Citation Information

Patent Citations

  • Chemical nickel-plating stabilizer and chemical nickel plating solution

    CN101831643A

  • Brightener for direct nickel plating of steel and iron elements and nickel plating solution thereof

    CN105088288A